Assessing the performance of Food Safety Management System using Food Safety Management System Diagnostic Tools and Microbial Assessment Scheme: A case of powdered beverage manufacturers - Cheah, Hua Yen; Merican, Suhaila Emma; Mahmud @ Ab Rashid, Nor Khaizura; Abu Bakar, Ainul Zakiah; Omar, Syaliza; Sanny, Maimunah (Universiti Sains Malaysia, 2021)
Background: The objective of the study is to assess the performance of the Food Safety Management System (FSMS) among powdered beverage manufacturers using Food Safety Management System Diagnostic Tools (FSMS-DI) and Microbial Assessment Scheme (MAS). Methods: FSMS-DI was used to evaluate the context factors, core control and core assurance activities of five powdered beverage manufacturers with different types of FSMS certification. Manufacturer A is not certified with any FSMS, while manufacturers B, C, D and E are complied with MeSTI, GMP, HACCP and ISO 22000, respectively. For MAS, samples were collected from the selected critical sampling locations of two manufacturers who complied FSMS with the least (manufacturer B) and the most stringent (manufacturer E) requirements. The samples consisted of two different types of powdered beverage products were analysed for total plate count (TPC), Salmonella, Escherichia coli, Staphylococcus aureus, yeast and mould count (YMC). Results: The food safety (FS) output of powdered beverages for manufacturer E was better (overall score of 3) than manufacturer B (overall score of 2–3). Manufacturer E was able to achieve their FS objectives. The FSMS activities of manufacturer C, D and E were better (overall score of 2–3) than manufacturer A and B (overall score of 1–2). Conclusion: The study demonstrated that FSMS-DI and MAS can be used to differentiate the FSMS performance of powdered beverage manufacturers with different types of FSMS certification. Higher scores of FSMS activities obtained by the manufacturer who complied with stringent FSMS certifications contributed to better microbiological safety performance of powdered beverages.